Anti-avoidance, amendments and anomalies: The impact of select anti-avoidance provisions and their subsequent amendments on employee share incentive schemes operating through trusts - Kleynhans, Marike (Department of Finance and Tax, 2019)
Employee share incentive schemes have become a common phenomenon in companies world-wide and are an established method of allowing the employee to hold equity in the company which in turn allows the employee to personally benefit from the growth and profitability of the company. In light of the fact that employees receive remuneration by virtue of their employment and through their participation in these employee share schemes, the tax treatment of this remuneration should be considered in terms of the South African taxation laws. The Income Tax Act 58 of 1962 has been amended over time so as to introduce various anti-avoidance rules aimed at preventing employee participants in these schemes from classifying income received by virtue of employment as either dividends or capital gains. These anti-avoidance provisions, contained in sections 8C and 10(1)(k)(i) and the Eighth Schedule to the ITA, have evolved since their introduction, so as to: 1. address any anomalies and to close perceived loopholes identified in terms of these provisions; and 2. to clarify the circumstances in which these provisions will find application. This study highlights the evolution of these anti-avoidance provisions and discusses (a) whether the amendments succeeded in addressing the anomalies and closing loopholes as intended; and (b) whether the amendments inadvertently created any additional anomalies. An analysis of the current wording of the anti-avoidance provisions is conducted and the impact these provisions on the most prevalent employee share schemes operating through trusts is explored, whereafter suggestions for further amendments to the ITA are proposed.